Dystopia and intertextuality in El año del verano que nunca llegó by William Ospina - Acevedo, Segura Yadira (Romanica Olomucensia, 2019)
The latest novel by the Colombian writer William Ospina, El año del verano que nunca llegó, is written on the basis of an important literary palimpsest, grounded in two great myths of nineteenth-century literature - Frankenstein, by the English writer Mary W. Shelley, and The Vampire, by the British author John William Polidori. Given the dystopian characteristics of Shelley's work, the study performed by Ospina in his novel focuses on Frankenstein, a story in which the creation of life and artificial intelligence finds its maximum expression in the irrational nature of one of the most famous monsters of universal literature. In this sense, intertextuality is an essential literary resource, insofar as it is what determines the dystopian nature of the work of the Colombian writer. El año del verano que nunca llegó, then, becomes a significant hypertext, an echo of a nineteenth-century dystopian text in a sort of pluridirectional flashback. Indeed, the author, rather than the literary diegesis, is interested in the network of pre-existing connections that made this myth created by the young writer possible. Thus, it can be concluded that, from the intertextual perspective, the work of William Ospina is fundamentally a dystopian story in which the author recreates a surprising novel, started in a night of a stormy summer in Switzerland, at the Villa Diodati, on the shores of Lake Geneva.
Keywords: dystopia; William Ospina; El año del verano que nunca llegó; Frankenstein; intertextuality